Lewis M. Haupt papers - Haupt, Lewis M. (Lewis Muhlenberg), 1844-; Haupt, Herman, 1817-1905.; Isthmian Canal Commission (U.S.); Nicaraguan Canal Commission (U.S.)
Correspondence, speeches, and articles relating to the selection of a route for an isthmian canal and to Haupt's efforts to secure the Nicaraguan route. Includes records of the Nicaraguan Canal Commission and the Isthmian Canal Commission such as work papers, reports, minutes, memoranda, drawings and charts, news clippings, and copies of congressional hearings, speeches, and proposed bills. Correspondents include Newton Diehl Baker, William Jennings Bryan, Andrew Carnegie, John Hay, John Tyler Morgan, and Theodore C. Search. Includes letterbook (1861-1863) of Haupt's father, Herman Haupt, concerning his duties as chief of construction and operation of the U.S. Bureau of Military Railroads.
In part, typewritten transcripts.
Civil engineer and public official of Pennsylvania. Died 1937.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Morgan, John Tyler, -- 1824-1907 -- Correspondence; Search, Theodore C. -- Correspondence; United States. -- Bureau of Military Railroads; Canals -- Nicaragua; Military railroads; Civil engineers; Public officials -- Pennsylvania